Extraction and Characterization of Endogenous Polygalacturonase Enzyme in Cocoa Pulp - Gandaputra, G. P.; Harijono, Harijono; Susanto, Tri; Kumalaningsih, Sri; Aulanni'am, Aulanni'am (Jurnal Teknologi Pertanian, 2007)
Endogenous polygalacturonase (PG) enzymes in cocoa pulp have not been studied yet. The research, aimed to extract and characterize endogenous PG enzymes in cocoa pulp, was carried in two steps: (i) extraction of endogenous PG enzyme and (ii) enzyme characterization i.e. enzyme activity assay and determination of enzymatic kinetics (Km and Vmax), molecular weight (MW) by electrophoresis, and determination of its optimum temperature and pH. The results showed that the characteristics of endogenous PG in cocoa pulp were as followed: the relative activity of 4,58Â± 0,06 Units/ml,Â  Vmax of 6,69 Units/ml, Km of 0,37 %, MW was 32,84 and 63,58 kDa, and the combination of temperature and pH optimum were 42,5oC and 4,6. Key words: endogenous polygalacturonase (PG), cocoa pulp